14 Exercise Programs To Decrease Pain In Athletes With Patellar Tendinopathy In-season: A Rct. (5th September 2014) - van Ark, Mathijs; Cook, Jill; Docking, Sean; Zwerver, Johannes; Gaida, James; van den Akker-Scheek, Inge; Rio, Ebonie
Abstract : Introduction: Many athletes with patellar tendinopathy are still participating in sports but have symptoms during or after activities. It is hard to decrease pain in-season with current treatments; eccentric exercises in-season have resulted in worsening of symptoms [Fredberg, 2008; Visnes, 2007]. Other exercise programs (isometric and isotonic exercises) have the potential to decrease pain while continuing sport activities [Kongsgaard, 2010; Naugle 2012]. The aim of this study was to compare an isometric against an isotonic exercise protocol designed to decrease patellar tendon pain in-season. Methods: Jumping athletes with patellar tendinopathy playing at least 3 times per week participated in this study. They were randomised into an isometric exercise or isotonic exercise group. The exercise programs consisted of 4 exercise sessions per week for 4 weeks. The exercise sessions consisted of 5 sets of 45 second isometric holds for the isometric group and 4 sets of 8 repetitions heavy slow resistance for the isotonic group; both exercises were performed on a leg extension machine. Pain during a Single Leg Decline Squat (SLDS) on a Numeric Rating Scale (0–10) was used as the main outcome measure. Participants kept a diary in which they scored the pre and post exercise pain scores when they performed an exercise session. A Generalised Estimating Equations (GEE) model was run with participants (id) as subject variable; main and interaction effects were determined for the factors time and type of intervention. Results: Preliminary results (n = 15) showed a significant improvement of both groups over time (Wald chi-square = 657.4, df =13, p ≤ 0.001). Both groups improved but showed a significantly different effect over time (interaction effect time by intervention, Wald chi-square = 3897.7, df =13, p ≤ 0. 001). This difference seems to take place in week 2 and 3 (Figure 1 ). There was no difference between groups (Wald chi-square = 0.438, df =1, p = 0.508). Discussion: Preliminary results showed that both isometric and isotonic exercises result in a decrease in pain in athletes with patellar tendinopathy symptoms over a 4 week period in-season. This is one of the first in-season studies that makes a direct comparison between exercise protocols for patellar tendinopathy and to our knowledge the first study to investigate isometric exercises in a clinical setting. A decrease in pain score in week 2 and increase in week 3 of the isometric group might possibly be explained by a fast decrease in pain which might have resulted in an increase in activities and a related increase in pain. Isometric and isotonic exercise programs are promising easy-to-use exercises to reduce pain from patellar tendinopathy for athletes in-season. References: Fredberg et al . Am J Sports Med. 2008;36:451–460 Kongsgaard et al . Am J Sports Med. 2010;38:749–756 Naugle et al . J Pain. 2012;13(12):1139–1150 Visnes H et al . Br J Sports Med. 2007;41(4):217–223